Tingkat pemanfaatan ikan delah (Caesio teres) pada Perairan Mapur yang didaratkan di Desa Kelong, Kecamatan Bintan Pesisir, Kabupaten Bintan, Indonesia - Rapella Desiani; Susiana Susiana; Febrianti Lestari (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2019)
The Mapur waters contain various kinds of fish caught in one of them is Yellow and blueback fusilier. Yellow and blueback fusilier is one of the catches of high economic vulued. High economic value can certainly boost the Yellow and blueback fusilier and can affect the population. The research was conducted from August 2018 to July 2019 at this fish landing on Kelong Village. The tools used are stationery, cameras and materials used are fish as a research object. The aims of this research was to determine the Maximume Sustainable Yield (MSY), rate and effort of utilization, and the amount allowed to catch (JTB) of Yellow and blueback fusilier in Mapur waters landing this on Kelong Village. This research used survey method with primary data retrieval using live fishermen interviews and secondary data consists of document or literature that supports the research. The result of this research is the potential value of MSY is 787,067 kg/unit whit the optimum effort (f opt) 1.280 unit/ month not over the limit in other words yet overfishing. The utilization rate of Yellow and blueback fusilier 42% medium level overall, and so if increased efforts are still possible to optimize the haul, but still controlled. And amount allowed to catch value Yellow and blueback fusilier is 629.65 kg/unit, that Yellow and blueback fusilier can still be improved for optimal results, but not beyond the determined limits.